Idiopathic retroperitoneal fibrosis: A report on 15 patients - Hadži-Djokić, Jovan; Pejčić, Tomislav; Bašić, Dragoslav; Vukomanović, Ivana; Džamić, Zoran; Aćimović, Miodrag; Radovanović, Milan (Vojnosanitetski pregled, 2015)
Background/Aim. Retroperitoneal fibrosis (RPF) represents a chronic pathological process characterized by fibrosis which entraps and compresses the ureters and the great blood vessels in the retroperitoneal space. A specific form of RPF is idiopathic RPF, an uncommon collagen vascular disease of unclear etiology. The series of 15 patients which underwent open surgical repair due to idiopathic RPF is presented herein. Methods. From 1989 to 2012, 11 male and 4 female patients underwent surgery due to primary RPF. The ureters were entrapped unilaterally (7 patients), or bilaterally (8 patients). Major symptoms included low back pain due to hydronephrosis (9 patients), uremia (4 patients), and urinary tract infection (2 patients). The diagnosis was based on intravenous urography (IVU), retrograde ureteropyelography and computed tomography (CT). Results. Surgical procedures included intraperitoneal ureteral displacement (8 patients) and ureteral wrapping with omental flap (6 patients). One patient underwent bilateral ureteral stenotic segments resection and oblique ureterography, followed by wrapping with omental flap. Pathological examination confirmed primary RPF in all patients. The mean operative time was 3.5 h (range 2.5–4.5 h). The average intrahospital stay was 21 days (range 16–26 days). The mean follow up was 32 months (6–46 months). During the follow up, 12 patients had improvement on IVU.  Conclusion. Early recognition of signs and symptoms of RPF is of the utmost importance for the outcome. Surgical procedures, including ureteral wrapping with omental flap, or intraperitoneal ureteral displacement, usually represent definitive treatment.
Keywords: retroperitoneal fibrosis; diagnosis; differential; urologic surgical procedures